CRISP3 expression drives prostate cancer invasion and progression. Issue 7 (July 2020) - Volpert, Marianna; Furic, Luc; Hu, Jinghua; O'Connor, Anne E; Rebello, Richard J; Keerthikumar, Shivakumar; Evans, Jemma; Merriner, D Jo; Pedersen, John; Risbridger, Gail P; McIntyre, Peter; O'Bryan, Moira K
Abstract : Identifying the factors stimulating prostate cancer cells migration and invasion has the potential to bring new therapeutic targets to the clinic. Cysteine-rich secretory protein 3 (CRISP3) is one of the most highly upregulated proteins during the transition of a healthy human prostatic epithelium to prostate cancer. Here we show using a genetically engineered mouse model of prostate cancer that CRISP3 production greatly facilitates disease progression from carcinoma in situ to invasive prostate cancer in vivo . This interpretation was confirmed using both human and mouse prostate cancer cell lines, which showed that exposure to CRISP3 enhanced cell motility and invasion. Further, using mass spectrometry, we show that CRISP3 induces changes in abundance of a subset of cell-cell adhesion proteins, including LASP1 and TJP1 both in vivo and in vitro . Collectively, these data identify CRISP3 as being pro-tumorigenic in the prostate and validate it as a potential target for therapeutic intervention.